How respiratory diseases were treated at the beginning of the 19th century - Starzyk, Jacek; Starzyk-Łuszcz, Katarzyna (Medical Studies/Studia Medyczne, 2014)
Respiratory diseases were quite common in the past. A treatment procedure for an acute respiratory disorder, most probably pneumonia, in a 72-year-old man was presented based on archival source materials dating from 1801. The treatment was provided by a doctor, barber surgeon “nurse” and pharmacist, who were practicing in Koniecpol in 1801. The patient was given mucolytic, antitussive, cardiac, antipyretic and analgesic medications and appetite stimulants. From the medical point of view that prevailed at that time, the treatment was correct. The patient was also given medications recommended under the humoral theory, which was still being followed at that time. According to that theory, the human body was thought to contain four humours: blood, phlegm, yellow bile and black bile. An imbalance of humours resulted in a disease. The treatment was designed to restore the proper humoral balance by techniques such as enemas, diuretics and bloodletting. From the present medical point of view, the treatment was incorrect. It caused anaemia and disturbances in water, electrolyte and acid-base homeostasis. The treatment resulted in the patient’s death. However, one can hardly blame doctor Tichi, as his treatment was fully compliant with the scientific views prevailing at that time.